Wahdatul Ulum Course Mobile Application Using Software Development Life Circle (SDLC) Method - Nasution, Yusuf Ramadhan; Hasugian, Abdul Halim (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
During a pandemic like now, ways to improve the quality of learning activities really require the application of technology and learning tools to support the process of teaching and learning activities. Technological developments make it easier to access existing learning tools. Today's learning tools must be accessible to many people and without any limitations of space and time. The application will be made as attractive and interactive as possible for its users. The application is designed to be mobile based and uses the Android operating system. Application development is supported by Google Android. The designed learning mobile device application includes syllabus, RPS, open materials and other supports. The application will be made as attractive and interactive as possible for its users. The application is designed to be mobile based and uses the Android operating system. Application development is supported by Google Android. The software development model used is the Software Development Life Circle (SDLC) model.